2022
DOI: 10.3389/fendo.2022.859332
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ovarian Reserves With an Increasing Number of Previous Early Miscarriages: A Retrospective Analysis

Abstract: The fact of ovarian reserve (OR) decreased in women with recurrent miscarriage has been well known. However, Whether OR would decrease with increasing numbers of previous miscarriages (PMs) is still unclear. To address this, OR parameters of following four groups’ patients were evaluated: 99 women with one previous miscarriage (PM1), 46 women with two previous miscarriages (PM2) and 35 women with three or more previous miscarriages (PM3). The control group included 213 women without a history of miscarriage (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…Our results are in contrast with previous meta-analytic findings ( Bunnewell et al , 2020 ; Busnelli et al , 2021 ; Tan et al , 2022 ). Reasons to explain this inconsistency can only be hypothesized.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are in contrast with previous meta-analytic findings ( Bunnewell et al , 2020 ; Busnelli et al , 2021 ; Tan et al , 2022 ). Reasons to explain this inconsistency can only be hypothesized.…”
Section: Discussioncontrasting
confidence: 99%
“… Cornille et al (2022) showed that, in women <37 years, low serum AMH level was not associated with an increase in the miscarriage rate after fresh blastocyst transfer. Two additional studies not considered in the meta-analyses as they were published later also merit consideration ( Tan et al ., 2022 ; Christensen et al , 2022 ). Tan et al (2022) showed significantly lower serum levels of AMH in women who had three miscarriages compared to those who did not have any.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review demonstrated an increased risk of diminished ovarian reserve (including that of lower AMH concentrations) in 155 women with RPL compared to 158 women without RPL (Bunnewell et al, 2020). In another recent study, the proportion of women with a low AMH increased with an increasing number of previous pregnancy losses, also when stratifying results according to the women's age (Tan et al, 2022). However, while there may be an association between AMH concentrations and women diagnosed with RPL, the clinically most important issue is whether there is an association with the risk of yet another pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%